natMg(p,p0) differential cross-section measurement relevant to the EBS technique - Alvanou, Eleni; Lagoyannis, Anastasios; Axiotis, Michael; Bligoura, Natalia; Harissopulos, Sotirios; Kokkoris, Michael -; Maragkos, Fotis; Ntemou, Eleni; Preketes-Sigalas, Kostas (HNPS Advances in Nuclear Physics, 2020)
In the present work the natMg(p,p0)natMg reaction was investigated in the energy range Ep,lab ~ 2700–4250 keV, at six backward detection angles (120o-170o) suitable for analytical purposes. The measurements were performed using the 5.5 MV TN11 HV Tandem Accelerator of N.C.S.R. ‘‘Demokritos”, Athens, Greece and a high-precision goniometer. The experimental data are compared to data from the literature, when available, and similarities and discrepancies are presented and analyzed.